Signs of myelin impairment in cerebrospinal fluid after osmotic opening of the blood-brain barrier in rats - Kozler, P; Sobek, O; Pokorný, J (Physiological research, 2015)
A number of clinical neurological pathologies are associated with increased permeability of the blood brain barrier (BBB). Induced changes of the homeostatic mechanisms in the brain microenvironment lead among others to cellular changes in the CNS. The question was whether some of these changes can be induced by osmotic opening of BBB in an in vivo experiment and whether they can be detected in cerebrospinal fluid (CSF). CSF was taken via the suboccipital puncture from 10 healthy rats and six rats after the osmotic opening of the BBB. In all 16 animals, concentration of myelin basic protein (MBP ng/ml), Neuron-specific enolase (NSE ng/ml) and Tau-protein (Tau pg/ml) were determined in CSF by ELISA. Values in both groups were statistically evaluated. Significant difference between the control and experimental group was revealed only for the concentration of myelin basic protein (p<0.01). The presented results indicate that osmotic opening of the BBB in vivo experiment without the presence of other pathological conditions of the brain leads to a damage of myelin, without impairment of neurons or their axons.
Keywords: encefalitogenní základní proteiny; myelinová pochva; tau Proteins; Myelin Sheath; proteiny tau; Phosphopyruvate Hydratase; Blood-Brain Barrier; Myelin Basic Protein; osmotický tlak; mužské pohlaví; Rats, Wistar; fosfopyruváthydratasa; Mannitol; zvířata; mannitol; biologické markery; permeabilita; Nerve Fibers, Myelinated; Permeability; potkani Wistar; Biomarkers; hematoencefalická bariéra; nervová vlákna myelinizovaná; Male; Osmotic Pressure; Animals